Two new species of Phylloporus (Boletaceae) from the montane cloud forest of Eastern Mexico - Gutiérrez-Domínguez, Erick; Montoya, Leticia; Ramos, Antero; Andrade-Torres, Antonio; Noa-Carrazana, Juan Carlos; Ortiz-Ceballos, Ángel Isauro; Bandala, Victor Manuel (Phytotaxa, 2024)
Phylloporus represents a group of fungi belonging to the lamellate Boletineae, which despite not having been exhaustively documented worldwide, most of its species have been recognized in tropical regions. The present research proposes the description of Phylloporus montanus and P. xalapensis as new species to science. Both were discovered in Mexico through a sampling focused on the study of the genus in the montane cloud forest from the east region of the country. The new species were recognized based on a morpho-anatomic study and supported by a phylogeny inferred from internal transcribed spacer (ITS rDNA), nuclear large ribosomal subunit (nLSU) and translation elongation factor 1-alpha (TEF1) sequences. Descriptions of each species are detailed, accompanied by illustrations and photographs.